Fostering Impactful Citizen Engagement - Jespersen, Ann-Sofie; Larizza, Marco; Schott, Berenike Laura (World Bank, Washington, DC, 2020)
Research on citizens as drivers of change and recent reports from the World Bank can inform its citizen engagement mandate. This governance note seeks to contribute to improving the World Bank's entry points for citizen engagement by operationalizing findings on social organizations from the World Development Report 2017: Governance and the Law (WDR 2017) and Citizens as Drivers of Change: How Citizens Use Human Rights to Mobilize, Effectively Engage with the State and Promote Transparency and Accountability. To accomplish this, taken from the second report are three real-world examples of citizens' initiatives to increase transparency and accountability in public service delivery. The note also consists of a brief outline of what the Bank is doing to promote citizen engagement, a summary of key lessons on what makes external support from international actors effective, and suggestions for next steps the Bank can take to best support citizen engagement in its operations.